TEORI-TEORI EKONOMI POLITIK INTERNASIONAL DALAM PERBINCANGAN: ALIRAN DAN PANDANGAN - Mohammad Maiwan (Jurnal Ilmiah Mimbar Demokrasi, 2015)
This article briefly describes some of the major theories of international political economy, namely: Liberal Trade Theory; Nationalist trade theory; The theory of "Dual Economy"; Theory of the Modern World System (MWS); Hegemonic stability theory. Each of these theories has shown an important aspect of economic and political relations. In addition to having the advantages of each, above theories also opened the weaknesses of another theory, allowing us to see the extent of his power in explaining trends in today's global economy. Each theory has its contextual truth respectively. In addition, any such theory can not stand alone. We need elements of each other's views to be aware of the complex relationship between economics and politics. In international relations the interrelationship or interplay between economic factors with the political factor is absolute.